Anti Phenolic Glycolipid I (PGLI) of salivary IgA/IgM from Mycobacterium leprosy for early detection of subclinical leprosy - Maria Andisa Mayangsari, - (DR. P. R. YADAV, 2020)
Leprosy is a chronic infectious disease caused by the bacterium Mycobacterium leprae. Indonesia is one of the countries with the highest leprosy, 3rd after India and Brazil. In 2013, Indonesia has 16.856 of new leprosy cases. In diagnosing leprosy, physical clinical examination not always able to detect the early phase of the disease. Therefore, we need a diagnostic tool that can detect infection with Mycobacterium leprae early so that treatment can be performed optimally. Saliva contains a lot of protein and nucleic acid molecules that reflect physiological and pathological status. Through saliva, anti Phenolic glycolipid 1 (anti-PGL1) dan be examined which is a specific antibody against PGL1 M. leprae found in the cell wall. Anti- PGL1is produced as a form of immune response against M. leprae. Individuals with a positive anti-PGL1 shown to have six times greater risk of developing leprosy. Serological examination by ELISA for detection of anti-PGL1 is potential to become a tool for early detection of subclinical leprosy (presence of bacilli), these results are useful to monitor and prevent the possibility of leprosy. Journal and other literature study searched with specific keywords. The result shows salivary anti-PGL1 is representative for M. leprae infection. Examination of anti-PGL1 in saliva can unlock the potential diagnosis of safe, sensitive and non-invasive to leprosy especially in endemic areas.